2017
DOI: 10.21660/2017.40.65948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacterial Quorum Sensing by the Ruminal Fluid of Cattle

Abstract: Rumen fluid contains factors that inactivate autoinducers, monitor microflora development and prevent the mobilization of virulence properties, and thus, the formation of resistant bacteria. The aim of this study was to assess the ability of rumen fluid to suppress the intercellular communication of bacteria by inactivating the N-acyl-homoserine lactones. We used strains of luminescent Escherichia coli JLD271 which were transformed with plasmids containing quorum sensing genes and luminescence genes. Bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…It is known that tannings may participate in modulation of the composition and activity of intestinal microflora and its interaction with the entering compounds. It is reported that gram-positive bacteria are more sensitive to plant-based extracts rich in tannin-like substances [28,29]. It is also confirmed by properties of compounds earlier found in Quercus cortex extract [12,13].…”
Section: Weigh (G) Dynamics In Crossmentioning
confidence: 57%
“…It is known that tannings may participate in modulation of the composition and activity of intestinal microflora and its interaction with the entering compounds. It is reported that gram-positive bacteria are more sensitive to plant-based extracts rich in tannin-like substances [28,29]. It is also confirmed by properties of compounds earlier found in Quercus cortex extract [12,13].…”
Section: Weigh (G) Dynamics In Crossmentioning
confidence: 57%
“…тором, лимитирующим эффективность животноводства, является дефицит микронутриентов, в том числе эссенциальных элементов, с последующим развитием ассоциированных патологий [5]. При этом коррекция уровня обмена отдельных металлов характеризуется снижением риска развития данных заболеваний и может в ряде случаев обладать стимулирующим влиянием на продуктивные качества сельскохозяйственных животных [6].…”
unclassified